South Africa : Detailed Assessment of Compliance on Basel Core Principles for Effective Banking Supervision. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
Banking supervision in South Africa has been effective in reducing the impact of the global financial crisis. The banks have remained profitable, and capital adequacy ratios have been maintained well above the regulatory minimum. The supervisory and regulatory framework has been strengthened substantially. A specific regulation dealing with country and transfer-risk regulation should be drafted. The registrar's remedial powers in banks should be strengthened. The Bank Supervision Department should expand its expertise in specialized areas such as operational risk and countering the abuse of financial services.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet